BREAK EVENT POINT PADA PENYUSUNAN ANGGARAN OPERASIONAL DI UNIVERSITAS XYZ - Hesti Zia Amelia; Indra Cahya Kusuma (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aims to determine the components, calculations, and magnitude of the break event and shutdown point in preparing the budget at XYZ University. This research is a quantitative descriptive research method. Calculating the BEP in compiling a university's operating budget is very important so that it can be known how many students are accepted to reach the breakeven point (BEP).